Smart Hospitals: Intelligent IoT Solutions for Enhanced Patient Experience and Workflow Optimization - Laxmaiah , M.; Neeraja , B.; Junnarkar , Aparna Atul; Kaur , Mandeep; Shaik , Nazeer (Research Highlights in Science and Technology Vol. 9, 2023)
This chapter examines the field of Intelligent Internet of Things (IoT) solutions, examining how they might improve patient satisfaction and streamline medical procedures in "smart hospitals." The chapter provides a comprehensive view of the current healthcare system, highlighting the difficulties faced by conventional medical facilities and the need for creative solutions. It delves into the core elements of smart hospitals, such as IoT devices, data analytics, and connectivity, as well as their various healthcare applications. The chapter conducts a thorough review of the literature and analyzes case studies in order to provide a current overview of smart hospital implementations. The topic of data security and privacy in smart hospitals is discussed in terms of both potential benefits and disadvantages. Finally, the chapter draws to a close by outlining potential future directions and highlighting the transformative impact of smart hospitals on healthcare delivery. The main goal is to demonstrate a thorough understanding of how innovative IoT solutions can transform hospitals into patient-centric healthcare settings, boosting productivity and satisfaction for both patients and healthcare providers.